Justice is indivisible: Palestine as a feminist issue - Elia, Nada (Decolonization: Indigeneity, Education & Society, 2017)
⠀⠀⠀⠀⠀⠀⠀⠀⠀
Keywords: approches et analyses; asie; cours; féminisme arabe; féminisme décolonial; histoire et politique; palestine; pol4212; premier cycle; ressource en ligne; régions géographiques; sofia; système colonial; systèmes d'oppressions; thématiques

Black history month: Diversity and the British female suffrage movement - Mukherje, Sumita (The Fawcett Society, 2017)
The fight for the female vote was not solely a British, or a ‘white’ concern, writes historian Sumita Mukherjee.
Keywords: approches et analyses; asie; cours; droits des femmes*; europe; fem1000; féminisme décolonial; inde; mouvements des femmes*; premier cycle; royaume-uni; régions géographiques; suffragettes; thématiques